Creating an Enabling Environment for Learning Chemistry: A Case of Using Mobile Phone Apps for Attitude Change in Resource Constrained Private Secondary Schools in Uganda - Luyima, Jimmy; Walimbwa, Michael; Sentongo, John (JRIIE, 2021)
Intrigued by reports ranking chemistry as one of the worst performed science subjects over the years at Uganda Certificate of Examination level, citing attitude towards the subject as one of the explanations, this study investigated the effect of integrating WhatsApp supported instructional resources in the out of classroom teaching learning process on students’ attitude towards the subject, as a possible intervention measure. The study used a mixed methods approach, taking on a quasiexperimental pretest –posttest none equivalent group design. The Solomon’s Four Group design was specifically employed because of its high internal and external reliability and validity. Data from a sample of 240 student respondents, distributed between two experimental and two control schools was analyzed using the SPSS Independent and Paired samples t-tests for quantitative data, to establish whether there was a statistically significant difference between the experimental and control groups. Qualitative data was analyzed thematically, which was collaborated with the quantitative data. It was found out and later concluded that, the integration of WhatsApp supported instructional resources outside the classroom setting improved students’ attitude towards chemistry with more students in experimental schools ranking the chemistry as one of the science subjects they liked most.
Keywords: WhatsApp, Mobile phone, Chemistry, Attitude, Teaching, Learning